Shifting sociality during primate ageing. (9th November 2020) - Machanda, Zarin P.; Rosati, Alexandra G.
Abstract : Humans exhibit major age-related shifts in social relationships along with changes in social and emotional psychological processes that underpin these behavioural shifts. Does social ageing in non-human primates follow similar patterns, and if so, what are the ultimate evolutionary consequences of these social shifts? Here we synthesize empirical evidence for shifts in social behaviour and underlying psychological processes across species. Focusing on three elements of social behaviour and cognition that are important for humans—propensities to engage with others, the positive versus negative valence of these interactions, and capabilities to influence others, we find evidence for wide variation in the trajectories of these characteristics across primates. Based on this, we identify potential modulators of the primate social ageing process, including social organization, sex and dominance status. Finally, we discuss how comparative research can contextualize human social ageing. This article is part of the theme issue 'Evolution of the primate ageing process'.